A low-complexity orthogonal matching pursuit based channel estimation method for time-varying underwater acoustic OFDM systems. (May 2019) - Qiao, Gang; Song, Qingjun; Ma, Lu; Wan, Lei
Abstract: In this paper, we propose a low-complexity Orthogonal Matching Pursuit (OMP) based channel estimation method in underwater acoustic (UWA) orthogonal frequency division multiplexing (OFDM) system, where the channel is time-varying and described by a limited number of paths, each characterized by path delay, path gain and path Doppler scale. In the proposed method, we calculate the candidate path signature Hermitian inner product matrix in advance, avoiding the repeated calculations at each iteration in conventional OMP method. To further reduce the complexity, we estimate the path gains by solving a least-squares (LS) problem after the whole iteration procedure instead of doing this at each iteration step in the conventional OMP method. Results of numerical simulation and sea trial demonstrate the effectiveness of the proposed method in time-varying UWA channels, which can achieve the comparable performance with much lower computational complexity compared with the conventional OMP method.